Eco-friendly alginate/PCL-TiO2 hybrid biocomposites: Preparation, properties, and methylene blue photodegradation - Bunga Fisikanta Bukit; Agus Wedi Pratama; Erna Frida; Bakti Berlyanto Sedayu; Dina Fransiska; Deni Purnomo; Emma Rochima; Istiqomah Rahmawati; Sona Suhartana; Firda Aulya Syamani (South African Journal of Chemical Engineering)
The study focuses on developing an environmentally friendly method for synthesizing hybrid biocomposites using sodium alginate, polycaprolactone (PCL), and TiO2 fillers. The eco-friendly alginate/PCL-TiO2 hybrid biocomposites were prepared using a Rheomixer Polylab OS. Various characterization techniques, including XRD, FT-IR, UTM, DSC, TGA, biodegradation testing, and methylene blue photodegradation, were employed to evaluate the properties of the composites. XRD analysis of the composites PA, PA-Ti1, PA-Ti3, and PA-Ti5 revealed an orthorhombic to tetragonal semicrystalline structure after added TiO2. FT-IR spectroscopy show sharp peak at 1721 cm⁻¹ represents C = O vibration, while characteristic CH stretching vibrations of PCL are evident at 2800–2900 cm-1. Furthermore, Ti-O-Ti bond appears at wave number 668.48 cm−1 and Ti-O-C appears at 1054.69 cm−1. The addition of TiO2 slightly reduced mechanical properties. TiO2 influence the compound mechanical performance, with a decrease in elastic modulus and corresponding increase in elongation at break with increasing TiO2 content. DSC analysis revealed that the composites with TiO2 displayed a single melting peak slightly above 50 °C, with a significant increase in ∆Hm with TiO2 content. TGA results showed that all samples exhibited two stages of decomposition. The first stage, occurring around 200 °C and the second stage, observed above 300 °C. The PA composite showed a mass reduction from 0.058 g to 0.052 g, similar to PA-Ti1 and PA-Ti3. However, PA-Ti5 composite showed a smaller mass reduction. Methylene blue solutions containing PA-Ti1, PA-Ti3, and PA-Ti5 composites exhibited a color change from blue to transparent after 24 h of irradiation, indicating MB degradation.